Influence of Insurance Status on Curve Magnitude in Adolescent Idiopathic Scoliosis in Mainland China. Issue 6 (September 2020) - Lin, Tao; Meng, Depeng; Yin, Jia; Ji, Zhe; Shao, Wei; Han, Meng; Lai, Aining; Gao, Rui; Zhou, Xuhui; Meng, Yichen
Study Design: Retrospective cohort study. Objectives: To determine whether there is an association between insurance status and curve magnitude in idiopathic scoliosis pediatric patients in mainland China. Methods: Medical records of patients with adolescent idiopathic scoliosis in 4 tertiary spine centers across China from January 2013 to December 2017 were analyzed. Data was extracted on insurance status, curve magnitude, recommended treatment at presentation, source of referral, and treatment initiated. Additional information was collected for patients requiring corrective surgery, including time from recommendation for surgery to surgery and clinically relevant parameters such as, postoperative complications, and pre-/postoperative Scoliosis Research Society–22 scores were also collected for patients requiring corrective surgery. Results: Of the 1785 patients included, 1032 were Urban Resident Basic Medical Insurance Scheme (URBMS) insured and 753 were New Rural Cooperative Medical Scheme (NRCMS) insured. NRCMS patients presented with a larger major curve than URBMS patients (32.9° ± 15.1° vs 29.3° ± 12.6°, P = .028). For patients having surgery recommended, NRCMS patients presented with a larger mean Cobb angle at the first presentation (57.7° vs 50.9°, P < .0001) and at time of surgery (61.3° vs 52.2°, P < .0001), and experienced a significantly longer time from surgery recommendation to decision for surgery. Complication rates were comparable between the 2 groups, except for pulmonary complications (NRCMS 7.3% vs URBMS 2.8%, P = .04). Postoperatively, patients covered by NRCMS insurance experienced greater overall improvement in health-related quality of life and were less satisfied with the treatments. Conclusions: This study shows that health insurance may influence the severity of scoliosis on presentation, with implications on early diagnosis and surgery time.